Commensal microbiota influence systemic autoimmune responses. (19th January 2015) - Van Praet, Jens T; Donovan, Erin; Vanassche, Inge; Drennan, Michael B; Windels, Fien; Dendooven, Amélie; Allais, Liesbeth; Cuvelier, Claude A; van de Loo, Fons; Norris, Paula S; Kruglov, Andrey A; Nedospasov, Sergei A; et al.
Abstract Antinuclear antibodies are a hallmark feature of generalized autoimmune diseases, including systemic lupus erythematosus and systemic sclerosis. However, the processes underlying the loss of tolerance against nuclear self‐constituents remain largely unresolved. Using mice deficient in lymphotoxin and Hox11, we report that approximately 25% of mice lacking secondary lymphoid organs spontaneously develop specific antinuclear antibodies. Interestingly, we find this phenotype is not caused by a defect in central tolerance. Rather, cell‐specific deletion and in vivo lymphotoxin blockade link these systemic autoimmune responses to the formation of gut‐associated lymphoid tissue in the neonatal period of life. We further demonstrate antinuclear antibody production is influenced by the presence of commensal gut flora, in particular increased colonization with segmented filamentous bacteria, and IL‐17 receptor signaling. Together, these data indicate that neonatal colonization of gut microbiota influences generalized autoimmunity in adult life.